Avaliação de ciclovias e ciclofaixas de Belém e Ananindeua utilizando os métodos AHP e IGGVC - FERREIRA, Victor Henrique (2023)
The objective of the research is to evaluate, in a multicriteria way and with data treated by the AHP methodology, the determination of the quality of some rigid and flexible pavements in the cities of Belém and Ananindeua through the limits of IGGVC. And for that, bike lanes and lanes were chosen on Avenida Augusto Montenegro, Avenida Marquês de Herval and Avenida Doutor Freitas in Belém, already in Ananindeua arterial 5-B, Travessa sn – 24, Avenida Dom Vicente Zinco and Travessa sn - 03. Avenues, arterials and sleepers were surveyed in loco using Balbo's catalog of pathologies, which includes defects common to asphalt and concrete pavements, defects in asphalt pavements and defects in concrete pavements. With this on-site survey, a general inventory of defects for each type of pavement was created. Then, a new sheet for the rigid and flexible floor was created, the inventory sheet of the five defects that most occur in each floor. After defining these five pathologies through the forms for each type of pavement, the construction of the AHP comparative perception questionnaire began, which consisted of hierarchizing pathological manifestations that had their responses verbally and qualitatively ordinal, so that, with the help of from Saaty's table, these verbal and qualitative responses were converted to discrete and continuous quantitative responses, which allowed the calculation of the weighting factor (FP), which is essential for determining the quality of cycle paths and cycle lanes by the IGGVC. From the calculation of the IGGVC it was possible to observe that we had two pavements of regular quality, one pavement of good quality and one of excellent quality